Exploring Students' Views on Forensic Accounting Courses within The Accounting Curriculum - Fifi Dwi Rahmah Septianingrum; Ambar Kusumaningsih (Finance : International Journal of Management Finance, 2024)
This study aims to understand and explore students' views regarding forensic accounting courses included in the accounting curriculum. This study uses a quantitative approach with a questionnaire as a data collection tool. In this study include the necessity, advantage, appropriate methods, and discussion topics regarding fraud. The research sample consisted of accounting students in Surabaya who had taken audit courses. The results showed that in the necessity variable, respondents felt that fraud cases had occurred more and more recently, and audit practices and forensic accountants were considered sufficiently responsive in detecting fraud. In addition, respondents also think that the demand for forensic accountant services will increase in the future. In the advantages variable, there are nine statements regarding the advantages of forensic accounting courses, all of which are responded positively by the average respondent. For the appropriate approach variable, respondents suggested that forensic accounting courses be made stand-alone courses in the curriculum. In addition, there were 13 choices of fraud discussion topics, all of which were responded positively to be integrated into forensic accounting courses. This research provides important insights into student perceptions of forensic accounting courses and can be used as a basis for more effective curriculum development.